Studi Penurunan Konsentrasi Besi (Fe) dan Tembaga (Cu) pada Air Lindi menggunakan Metode Elektrokoagulasi dengan Elektroda Alumunium - Setiyono, Fery; Rosdiana, Rosdiana; Wibowo, Dwiprayogo (Universitas Muhammadiyah Kendari, 2025)
In processing leachate, various biological processing processes have been carried out, however processing is needed to reduce inorganic content such as heavy metals in leachate water. Electrocoagulation is an alternative liquid waste treatment that uses the principles of electrolysis, coagulation and flocculation. The aim of the research is to analyze the effect of electrical voltage using aluminum electrodes on reducing the concentration of Fe and Cu metals in leachate water, then calculate the efficiency of reducing Fe and Cu metals from each electrical voltage treatment given in this study, namely 6, 12 and 18 volts with a contact time of 60 minutes. The method used in this research is quantitative, experimental on a laboratory scale. The research results showed that the optimum metal content reduction reached 0.0288 mg/L and 0.0086 mg/L with an efficiency of 97.75% and 82.05% for Fe and Cu parameters respectively at a treatment voltage of 18 volts. These results show that the leachate treatment process using electrocoagulation techniques has great efficiency.